Performance of the lightning air terminal for the macro model of buildings - Baharom, Md. Nor Ramdon; Zainal, Zainab; Mahmod, Luqman Hakim; Ahmad, Hussein; Ullah, Irshad (United Kingdom Simulation Society, 2016)
"Lightning is a natural occurring phenomenon having a very high voltage and current. Building protection from the effect of lightning stroke is one of the most important features. Lightning flash, nature changes with increasing the clearance between the ground structure and the cloud. Providing proper protection to the building, Frankling rod/Lightning air terminal is an essential element to receive the lightning flashes in order to make sure the protection of building. In this paper a down scaled building with four lightning rods has been chosen to see how the lightning rods with different air gap and view of the building perform, in lightning flash. The building is tested with three different views which are front, back and side views. The lightning rods provided different air gaps/clearance between the plain and the top plate. Single stage impulse generator is used. A voltage up to 90 kV is applied to analyze the lightning flash receiving ability of lightning rods. Through experimental work the lightning flash receiving ability is studied in detail for three views of the down scaled building."